ANALISIS BAHAN BANGUNAN PADA DAERAH RAWAN GEMPA DAN TSUNAMI DI PESISIR PANTAI TELUK PALU - Fitriani, Tengku (Jurusan Teknik Sipil Universitas Tadulako, 2014)
This article points out building materials used in public dwellings in Teluk Palu shore. Based on materials used, types of buildings in Teluk Palu sea shore are devided into three: buildings made from bricks, concrete blocks, and timbers. The bricks and concrete blocks used are according the quality standards. The timbers are also commonly used, those are the second class/good quality. However, the timbers are not treated properly (not being preserved before used). Principles of building methods is revealed here. Keywords: building materials, conditions of houses, principles of earthquake and and tsunamiÂ Â resistant houses